The failure processes analysis of rock slope using numerical modelling techniques. (September 2017) - Tang, S.B.; Huang, R.Q.; Tang, C.A.; Liang, Z.Z.; Heap, M.J.
Abstract: The slope failure process includes crack initiation, propagation and coalescence during the formation of a slip surface (small deformation stage) and block movement, rotation and fragmentation during the sliding process (large deformation stage). Neither the finite element method (FEM) nor the discontinuous deformation analysis method (DDA) can solve such problems satisfactorily due to the complex mechanical behaviour of slope failure. To study the entire process of slope failure, we develop here a model that combines the FEM and DDA approaches. The main concept of this approach is to first apply FEM to model crack growth behaviour and then automatically switch to the DDA module to model the post-failure process when the slip surface forms. The efficiency and simplicity of this approach lies in keeping the FEM and DDA algorithms separate and solving each equation individually. The heterogeneous nature of the slope material at the mesoscopic level is considered by assuming that the mechanical properties of individual elements follow a Weibull statistical distribution. The slope models are progressively destabilized by the critical gravity approach, and both the failure onset and the slope collapse process are analysed. Our modelling reveals that shear cracks first initiate at the toe of slope and subsequently promote the propagation of tensile fractures due to the stress accumulation at the shear crack tips. Throughout the entire failure process, failure in tension occurs at a higher rate than shear failure and plays a dominant role in the formation of the slip surface. The effects of slope angle and pre-formed cracks on the post-failure process are studied using the proposed method. This study demonstrates that the modelling approach outlined herein is able to tackle the fundamental problems of rock slope failure and offers a better understanding of the slope failure mechanisms at both the macroscopic and microscopic levels. Highlights: A combined FEM and DDA method is proposed to study slope stability. Both the failure onset and the slope collapse process are analysed. Tensile failure plays a dominant role in the formation of slip surface. Shear cracking is the source of tensile cracks at the beginning of slope failure. The slide distance increases with increasing slope angle.